Pengembangan Media Pembelajaran Matematika Berbasis Komik Elektronik Dengan Menggunakan Landbot.Io - Mubarok, Faruq; Wintarti, Atik (MATHEdunesa, 2025)
Mathematics learning is often perceived as difficult by students due to the abundance of formulas and abstract concepts. This affects students' motivation and often results in poor understanding. Even before the lesson begins, students may assume that the material is too difficult, leading them not to try at all. This study aims to develop an interactive digital comic-based learning media using the Landbot.io platform. With engaging visual and interactive elements, the media is expected to increase students’ learning motivation and significantly improve their understanding. Landbot.io was selected due to its cost-free nature and user-friendly interface, making it accessible even to individuals without any previous experience in chatbots, catering to both developers and users. This study employs a Research and Development (R&D) approach, involving six 7th-grade students: two classified as having low abilities, two as having moderate abilities, and two as having high abilities. This aims to determine whether the media is effective for all cognitive levels. Data were collected through pretests and posttests to assess the effectiveness of the media. The results showed an improvement in students’ mathematics learning outcomes after using the media. Therefore, the media is considered effective in supporting conceptual understanding through visual and interactive approaches. Although there is still room for improvement, the media is generally suitable for classroom use.